Morfotektonika Wału Trzebnickiego (Śląskiego) = Morphotectonics of Trzebnica (Silesian) Ridge - Markiewicz, Andrzej; Winnicki, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Trzebnica (Silesian) ridge is an important morphological element of SW part of Polish Lowland - between valleys of Nysa Łużycka and Prosna rivers. This positive form has very complicated geology of Cenozoic stage with presence of deep glacitectonic deformations.
Keywords: X jubileuszowe sympozjum glacitektoniki